2014
DOI: 10.1007/s11695-014-1363-2
|View full text |Cite
|
Sign up to set email alerts
|

Argon Plasma Coagulation of Gastrojejunal Anastomosis for Weight Regain After Gastric Bypass

Abstract: Our study indicates that the use of APC to treat weight regain after RYGB is a safe and effective procedure and promotes a reduction in gastrojejunal anastomosis, final weight, and BMI, with a low rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1
11

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 24 publications
(31 reference statements)
2
72
1
11
Order By: Relevance
“…Alternatively, endoscopic techniques have recently been developed to treat weight regain. These include sclerotherapy where sodium morrhuate is injected around the GJA to reduce the GJA size,31 32 argon plasma coagulation,33 34 endoscopic plication and endoscopic suturing to close a small gastrogastric fistula and/or to reduce the size of the GJA 35–39. A recent multicentre, randomised, blinded, sham-controlled trial has provided level I evidence to support the use of sutured TORe procedure to treat weight regain following RYGB.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, endoscopic techniques have recently been developed to treat weight regain. These include sclerotherapy where sodium morrhuate is injected around the GJA to reduce the GJA size,31 32 argon plasma coagulation,33 34 endoscopic plication and endoscopic suturing to close a small gastrogastric fistula and/or to reduce the size of the GJA 35–39. A recent multicentre, randomised, blinded, sham-controlled trial has provided level I evidence to support the use of sutured TORe procedure to treat weight regain following RYGB.…”
Section: Discussionmentioning
confidence: 99%
“…These complications must be treated by a multidisciplinary team, with endoscopic evaluations playing a fundamental role [3]. Up to 20% of the patients submitted to treatment tend to have weight regain 5–10 years after the surgical procedure [4]. The causes of this weight regain are numerous, but they include metabolic dysfunctions, relaxed diets, a sedentary lifestyle, hormonal changes, fistulas, a large stomach pouch, and dilatation of the gastrojejunal anastomosis [3-6].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Aly [14] reported a case of APC in a patient with weight regain after RYGB that produced satisfactory results and concluded that this technique is effective and safe. Baretta et al [4] evaluated the safety and efficacy of APC in a study that included 30 patients with weight regain after RYGB who had dilatation of the gastrojejunal anastomosis. Each patient underwent 3 sessions of APC at 8-week intervals.…”
Section: Discussionmentioning
confidence: 99%
“…desenvolviam estenoses esofágicas (Aly, 2009); idealizou então que a realização da ablação da mucosa na face gástrica da AGJ levaria à redução intencional do diâmetro da mesma; desta forma, esta técnica consiste na eletrocoagulação da mucosa sem contato direto com o tecido, através da qual a energia elétrica é aplicada ao ionizar-se gás de argônio; realiza-se o procedimento induzindo uma queimadura controlada em toda a circunferência da anastomose; o posterior processo cicatricial induz fibrose e consequentemente redução no seu diâmetro; o procedimento pode ser repetido até três vezes para que esta atinja o diâmetro desejado (Baretta et al, 2015). -Sutura endoscópica: a técnica de sutura endoscópica visando redução do diâmetro da AGJ foi descrita por Schweitzer (2004); baseava-se no racional então empregado no tratamento endoscópico da doença do refluxo gastroesofágico, através do estreitamento do cárdia com máquinas de sutura ou plicatura mecânica; basicamente, dois tipos de mecanismos de preensão tecidual eram utilizados: os de sucção e os de tração através de pinças, antes da passagem do ponto ou locação da plicatura; inicialmente, as máquinas de sutura atingiam apenas espessura parcial da parede, mas seu aprimoramento permitiu posteriormente que realizassem pontos de espessura total (atingindo até a camada serosa) (Kumar e Thompson, 2014); pontos de espessura total teoricamente possibilitariam suturas mais duradouras com força de tensão maior e consequentemente melhores resultados no tratamento do reganho de peso (Kumar et al, 2014a); assim, esta técnica envolve a aplicação de pontos ao redor da AGJ com auxílio de acessório de sutura acoplado geralmente a um gastroscópio terapêutico de duplo canal;…”
Section: O Tratamento Endoscópico Do Reganho De Pesounclassified
“…(Ryou et al, 2009;Mullady et al, 2009;Mikami et al, 2010;Hornag et al, 2010;Leitman et al, 2010;Raman et al, 2011;Thompson et al, 2012;Jiraponyo et al, 2013;Ong'uti et al, 2013;Sung et al, 2013;Goyal et al, 2013;Eid et al, 2014;Arellano, 2014;Kumar e Thompson, 2014ae 2014bGoyal et al, 2015;Landi et al, 2016;Gallo et al, 2016;Kumar e Thompson, 2016;Patel et al, 2016;Vargas et al, 2016;Schulman e Thompson, 2016;Riva et al, 2017); três, sutura de espessura parcial (SEP) (Roll e D'Assumção, 2010; Thompson et al, 2013;Kumar e Thompson, 2014a); dois estudos relataram uso de APC (Baretta et al, 2015;Fittipaldi-Fernadez e Diestel, 2015); e um de OTSC (Heylen et al, 2011). Nenhum estudo descrevendo a escleroterapia satisfez os critérios de elegibilidade.…”
Section: Seleção Dos Estudos E Extração Dos Dadosunclassified